Efficacy of three therapy approaches in preschool children with cerebral palsy: a randomized controlled trial. (24th November 2015) - Kruijsen‐Terpstra, Anne J A; Ketelaar, Marjolijn; Verschuren, Olaf; Gorter, Jan Willem; Vos, Rimke C; Verheijden, Johannes; Jongmans, Marian J; Visser‐Meily, Anne
Abstract : Aim: To examine the efficacy of child‐focused, context‐focused, and regular care approaches, delivered in a rehabilitation setting by physical or occupational therapists to preschool children with cerebral palsy (CP), in optimizing the child's self‐care and mobility capabilities. Method: A multicentre randomized controlled trial clustered at therapist level was conducted in 13 rehabilitation centres. It included 68 children with CP (38 males, 30 females; mean age 3y, SD 6mo, range 1y 11mo–4y), classified as Gross Motor Function Classification System levels I to IV, who were already receiving therapy. Children received a child‐focused, context‐focused, or regular care approach during a 6‐month period. Self‐care and mobility capabilities were assessed with the Functional Skills Scale of the Pediatric Evaluation of Disability Inventory. Results: The child‐focused, context‐focused, and regular care approaches all resulted in significant but similar improvements in self‐care (regular: reference; child‐focused: β =−0.11, 95% confidence interval [CI] −0.68 to 0.46; context‐focused: β =0.13, CI −0.38 to 0.64) and mobility (regular: reference; child‐focused: β =−0.09, CI=−0.93 to 0.75; and context‐focused: β =0.14, CI −0.65 to 0.94) capabilities. Interpretation: The results suggest that the three therapy approaches were equally efficacious for preschool children with CP. Depending on a child's individual situation each approach can be selected. What this paper adds: In preschool children with cerebral palsy, a child‐focused approach, a context‐focused approach, and a regular care approach resulted in similar improvements in self‐care and mobility capabilities. There was no intervention effect on children's motor skills and participation, or on their parents' participation, quality of life, stress, or empowerment. The choice to use one of the three approaches should be based on the child's individual situation. This article is commented on by Harvey on pages658–659 of this issue.